2012
DOI: 10.1371/journal.pone.0036724
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of EP4 Signaling Attenuates Aortic Aneurysm Formation

Abstract: BackgroundAortic aneurysm is a common but life-threatening disease among the elderly, for which no effective medical therapy is currently available. Activation of prostaglandin E2 (PGE2) is known to increase the expression of matrix metalloproteinase (MMP) and the release of inflammatory cytokines, and may thus exacerbate abdominal aortic aneurism (AAA) formation. We hypothesized that selective blocking of PGE2, in particular, EP4 prostanoid receptor signaling, would attenuate the development of AAA.Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 36 publications
6
75
1
1
Order By: Relevance
“…Our data allow us to speculate that the COX-2/mPGES-1/EP-4 axis in MVEC is relevant for the PGE 2 -mediated hypervascularization of AAA from the early stages of human AAA development. Our data are also consistent with reports showing that suppression of either COX-2, mPGES-1, or EP-4 expression reduces AAA development in animal models ( 15,16,19,20 ), and reinforce the potential of mPGES-1 and EP-4 as alternative targets for therapy in AAA patients. modest increase of mPGES-1 found in AAA is the breakdown of VSMCs in AAA.…”
Section: Ep-4-activation-mediated In Vitro Angiogenesissupporting
confidence: 92%
See 2 more Smart Citations
“…Our data allow us to speculate that the COX-2/mPGES-1/EP-4 axis in MVEC is relevant for the PGE 2 -mediated hypervascularization of AAA from the early stages of human AAA development. Our data are also consistent with reports showing that suppression of either COX-2, mPGES-1, or EP-4 expression reduces AAA development in animal models ( 15,16,19,20 ), and reinforce the potential of mPGES-1 and EP-4 as alternative targets for therapy in AAA patients. modest increase of mPGES-1 found in AAA is the breakdown of VSMCs in AAA.…”
Section: Ep-4-activation-mediated In Vitro Angiogenesissupporting
confidence: 92%
“…EP-2 and EP-4 are both Gs-protein coupled receptors that upregulate intracellular cAMP levels, whereas EP-3 usually counteracts EP-2-and EP-4-mediated upregulation of cAMP by preferentially coupling to Gi proteins ( 17 ). Recently, confl icting results have been reported on the role of EP-4 in AAA development in animal models (18)(19)(20). These studies have been focused on the involvement of EPs in the activation of leukocytes (mainly macrophages) and VSMCs, and in the release of proteases during the immuneinfl ammatory process associated to AAA.…”
Section: Analysis Of Pgementioning
confidence: 99%
See 1 more Smart Citation
“…In our previous report, analyses of human aortic aneurysmal tissues demonstrated that EP4 expression is greater in aneurysmal legions than that in nondiseased areas. 49 Further studies are required to investigate whether EP4-mediated LOX regulation plays a role in pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous report, analyses of human aortic aneurysmal tissues demonstrated that EP4 expression is greater in aneurysmal legions than that in nondiseased areas. 49 Further studies are required to investigate whether EP4-mediated LOX regulation plays a role in pathological conditions.Taken together, these findings suggest that PGE 2 -EP4 signaling inhibits elastogenesis in the DA by degrading LOX protein.The PGE 2 -EP4-mediated LOX protein regulation via a previously unrecognized signaling pathway may also provide the basis for therapeutic strategies that target vascular elastogeneis. …”
mentioning
confidence: 99%